Penerapan Pembelajaran PAI Berbasis Kehidupan Living Values Education (LVE) - Yusi Srihartini; Chaerunnisa; Ade Maulana Saputra; Alimuddin (At-Tadris: Journal of Islamic Education, 2025)
Islamic education learning has not yet been seen to have a significant impact. The teaching and learning process in Islamic education tends to be more theoretical and less relevant to everyday life. The implementation of religious teachings is often only symbolic and ritualistic. In the learning process activities, an approach to learning is needed to achieve the desired learning objectives. One of them is the life-based learning approach Living Values ​​Education (LVE). This study aims to analyze the application of Islamic Religious Education learning based on life Living Values ​​Education (LVE). The research method used is the Literature review method. Sources of information can be books, journals, e-books, or other scientific articles. The results of this study indicate that the application of Islamic Religious Education (PAI) learning that focuses on everyday life has a significant effect on the understanding and practice of religious teachings among students. The research findings indicate that students involved in Islamic Religious Education learning with a life approach experience progress in several aspects, such as: Increasing Understanding of Religious Concepts, Practice of Religious Values, Student Involvement in the learning process, and Character Development. Overall, this study emphasizes that PAI learning based on daily life not only improves students' academic understanding, but also strengthens the implementation of religious values ​​and character development, which are very important in building a generation with good morals.